Sistem Informasi Tes Penerimaan Mahasiswa baru Pada Perguruan Tinggi XYZ Berbasis Web - Putu Andhika Kurniawijaya; I Wayan Widi Karsana (Universitas Nusa Cendana, 2022)
The challenge during this pandemic is for universities to carry out entrance exam selection while still implementing health protocols set by the government. The public's fear of Covid 19 makes parents of prospective students reluctant to give permission for prospective students to come directly to universities to take admission tests carried out by universities. With the development of technology and communication, it is now possible to take a new student acceptance test without having to come to the destination college. By utilizing web application technology, prospective students will be able to carry out written exams and interviews in one web application via the internet. So that the health protocol can still be implemented by universities without limiting the number of participants who will take the test. The research method used is the waterfall method starting from analysis, design, coding and testing. This new student admission test information system was built using the PHP programming language. The result of this research is a new student entrance examination information system that makes it easier for universities to carry out online admission tests.